Content of Lead (Pb) in Tilapia (Oreochromis niloticus) at the outlet of the Koto Panjang Reservoir, Kampar Regency - Yanti, Efrida; Budijono, Budijono; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Koto Panjang Reservoir has been contaminated by lead (Pb) and accumulated in fish. The reservoir inundation flow ends at the reservoir outlet inhabited by tilapia (Oreochromis niloticus) which can accumulate high amounts of Pb. This study aims to determine the content of Pb in the gills and muscles of tilapia. The fishing survey was conducted in August - September 2021. Samples of gills and muscles of tilapia (O. niloticus) is taken from the catches of local fishermen. Pb content analyzed after acid extraction. The results showed that the lead (Pb) content in the gills was 0.0567 mg/kg higher than in the muscles (0.0049 mg/kg) and the content was still below the threshold so it was suitable for consumption.Keywords: Lead gill,muscles reservoir tilapia